Assisted Natural Regeneration as a Tool for Forest Rehabilitation under JFM - an Analysis of Current Processes and Scope of Refinement - Bansal, A. K.; Choudhury, P. R.; Gogate, M. G. (Indian Forester, 2011)
Assisted/Aided Natural Regeneration (ANR) forms the major strategy of treating degraded forest through Joint Forest Management (JFM) approach under the National Afforestation Plan (NAP) and Externally Aided forestry Projects (EAP). It is the dominant plantation model of forest-treatment in India. Field implementation and practices, as the review of experiences in Maharashtra and in Orissa indicates, differs considerably from the prescriptions and provisions outlined for ANR models. ANR prescriptions and practices also do not align with the current forest policy with a thrust on community partiCipation, livelihoods improvement and biodiversity conservation. Policy envisaged that adoption and sustainability of Joint Forest Management (JFM), is incumbent upon a more community-sensitive, silviculturally apt ANR practices. Recognition of these concerns led Orissa Forestry Sector Development Project (OFSDP) to start a journey towards a refined ANR process. Step-by-step process developed follows a 'diagnostic and design' approach with the involvement of the community, the Forest Department and the non-governmental organizations (NGO). The process used GIS maps, local ecological knowledge and working plan prescriptions to analyze 4 ha-grids from eco-livelihoods perspectives and jointly develop grid-wise treatment plans. With formalized involvement of communities and NGOs in forest management, this refined process, JFM+, addresses upfront concerns of livelihoods and biodiversity, while reiterating commitment towards enriching forests and enhancing their productivity through thinning, seeding, under-planting, etc.